2018
DOI: 10.1017/ice.2018.197
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study using telehealth to implement antimicrobial stewardship at two rural Veterans Affairs medical centers

Abstract: This pilot study has successfully demonstrated the feasibility of using telehealth to support antimicrobial stewardship at rural VAMCs with limited access to local infectious disease expertise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…Infection prevention resources could be made available in lower complexity and entirely ambulatory centers through educational, telemedicine and policy sharing initiatives. Underscoring the potential for a telehealth solution, a promising recent VA pilot study demonstrated the feasibility and effectiveness of a telemedicine-based antimicrobial stewardship program for expanding these programs to rural health centers that have minimal ancillary support services [28]. In addition, measures to include existing staff in these facilities, such as incorporating local clinical pharmacists for antimicrobial stewardship interventions, may be another important approach to improve care without requiring additional hiring, which may present logistical and financial challenges for some centers, particularly those serving rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…Infection prevention resources could be made available in lower complexity and entirely ambulatory centers through educational, telemedicine and policy sharing initiatives. Underscoring the potential for a telehealth solution, a promising recent VA pilot study demonstrated the feasibility and effectiveness of a telemedicine-based antimicrobial stewardship program for expanding these programs to rural health centers that have minimal ancillary support services [28]. In addition, measures to include existing staff in these facilities, such as incorporating local clinical pharmacists for antimicrobial stewardship interventions, may be another important approach to improve care without requiring additional hiring, which may present logistical and financial challenges for some centers, particularly those serving rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the implementation of the VAST differed between sites A and B, with each team making adaptations to suit their system and culture. 4 This pilot project was not designed to test for the relative influences of differences in implementation; further investigation is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…A multidisciplinary team from each intervention site paired with an off-site infectious disease physician from another VAMC for weekly 1-hour telehealth sessions to discuss concerns related to infections and antimicrobial use among patients at the intervention site. 4 For site A (27 acute-care beds with limited capacity for ventilated patients; 162 long-term care beds), the VAST formed in August 2016. For site B (10 acute-care beds with no capacity for ventilated patient; 180 long-term care beds), the VAST formed in October 2016.…”
Section: Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monkowski and colleagues provided ID telemedicine consults, while Tande and colleagues provided asynchronous ID eConsult for remote hospitals, but neither described an integrated ASP component [ 9 , 10 ]. Stevenson and colleagues used a weekly videoconference to support antibiotic stewardship efforts at 2 rural facilities [ 11 ]. In a more integrated model, Laible and colleagues established an ASP across a rural health system through a daily call where local pharmacists identified and presented cases [ 12 ].…”
mentioning
confidence: 99%